Effects of 1998 Bleaching Event on a Large Pavona Clavus Colony in a Philippine Marine Protected Area - Solandt, Jean-Luc; Harding, Simon P.; Beger, Maria; Dacles, Terence P.; Raines, Peter (Silliman Journal, 2022)
In September 1998, with water temperatures at 31° Celsius, the initial bleaching event spread over the whole of the Visayas region. Bleaching reduced much of the live coral at Danjugan Island to dead coral covered with filamentous algae within six months. Acropora spp. corals associated with the Pavona colony were most susceptible to bleaching. This same colony suffered live tissue loss in shallow (6m) areas. The original live coral cover of 80% was reduced to approximately 5%, with dead coral heads subsequently covered by filamentous and macroalgae. Over two years the team from the Coral Cay Conservation investigated the effects of coral bleaching on a single colony of Pavona clavus at three depths at Danjugan Island, Negros Occidental, Philippines. Repeat monitoring of the area showed considerable recovery of Pavona clavus at medium depths (around 12m) from totally bleached live coral tissue cover to 88% healthy pigmented tissue by August 2000. This study highlights the important effect that depth at one site can have on coral bleaching and subsequent recovery within a single species of massive coral.